2021
DOI: 10.3389/fpls.2021.788377
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Integrated With Metabolomics Reveal the Effects of Ultraviolet-B Radiation on Flavonoid Biosynthesis in Antarctic Moss

Abstract: Bryophytes are the dominant vegetation in the Antarctic continent. They have suffered more unpleasant ultraviolet radiation due to the Antarctic ozone layer destruction. However, it remains unclear about the molecular mechanism of Antarctic moss acclimation to UV-B light. Here, the transcriptomics and metabolomics approaches were conducted to uncover transcriptional and metabolic profiling of the Antarctic moss Leptobryum pyriforme under UV-B radiation. Totally, 67,290 unigenes with N50 length of 2,055 bp were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…The Antarctic terrestrial and maritime ecosystem suffers from a variety of harsh climatic conditions like extreme dryness, low temperature, high UV-B radiation, extremely short growing season, all of which severely limit the growth and development of plants ( Convey and Peck, 2019 ; Perera-Castro et al, 2021 ; Liu et al, 2021b ). Lichens and bryophytes as well as two native Antarctic vascular plants Deschampsia antarctica and Colobanthus quitensis dominate the vegetations of Antarctica Peninsula ( Robinson et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Antarctic terrestrial and maritime ecosystem suffers from a variety of harsh climatic conditions like extreme dryness, low temperature, high UV-B radiation, extremely short growing season, all of which severely limit the growth and development of plants ( Convey and Peck, 2019 ; Perera-Castro et al, 2021 ; Liu et al, 2021b ). Lichens and bryophytes as well as two native Antarctic vascular plants Deschampsia antarctica and Colobanthus quitensis dominate the vegetations of Antarctica Peninsula ( Robinson et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, some 2-ODD genes from S. moellendorffii and P. patens were also annotated as probable ANS. Furthermore, six anthocyanin compounds including peonidin 3-O-glucoside chloride, peonidin O-hexoside, pelargonidin, malvidin 3-O-glucoside, cyanidin 3-O-galactoside, and cyanidin 3-O-rutinoside were recently confirmed to be present in Antarctic moss Leptobryum pyriforme by a widely targeted metabolomics, and cyanidin 3-O-rutinoside was the significantly up-regulated metabolite with log2(Fold change) 14.68 under ultraviolet-B radiation (Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, a significant increase was found in biological activity over the past 50 years, measured through moss growth or accumulation rates (Amesbury et al, 2017). Currently, Antarctic plants appears to be promising models for studying the adaptation mechanism to various abiotic stresses (Convey and Peck, 2019;Perera-Castro et al, 2020;Bertini et al, 2021;Liu et al, 2021) and monitoring the regional climate changes (Amesbury et al, 2017;Lee et al, 2017;Robinson et al, 2018;Cannone et al, 2022) as well as assessing the impact of human activities (Malenovský et al, 2015;Hughes et al, 2020). Particularly, the genomic features were widely clarified in the Antarctic bacteria (Benaud et al, 2021), algae (Zhang et al, 2020b), and fishes (Kim et al, 2019), but the underpinnings remain unclear in the adaptation of mosses to extreme environments.…”
Section: Introductionmentioning
confidence: 98%
“…The field experiments demonstrated that continuing UV-B radiation reduced the chlorophyll contents in the Antarctic moss (Bryum argenteum) and lichen (Umbilicaria aprina), and increased the contents of UV-B absorbing compounds (Singh and Singh, 2014). The Multi-omics analysis indicated that UVR8-mediated signaling, flavonoid biosynthesis, and DNA repair machinery might facilitate the adaptation of Antarctic moss to UV-B radiation Liu et al, 2021). The moderate moss Physcomitrella patens was more qualified of surviving UV-B radiation than Arabidopsis, and several flavonoid biosynthesis genes were also markedly upregulated in response to UV-B radiation (Wolf et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation